Termite biology in urban areas of Central Punjab Pakistan - Azeem, Muhammad Waqar (Dialogue Social Science Review (DSSR), 2024)
Abstract The current study is design to explore the biology, distribution behavior and some of impacts in urban areas located at Central Punjab, Pakistan. The research includes termite species identification, their behavioral ecology and impacts on urban infrastructure. It further reviews the existing termite management options and discusses urban planning, as well as climatic changes relative to termites. The research showed there to be four primary species of termites i.e. Odontotermes obesus, Microtermes obesi and Coptotermeis heimi that exhibit different distributional patterns as well as behavioral aspects. Extensive damage to existing infrastructure, largely in older housing and commercial buildings due to termites alone requires a more holistic approach than the reactive nature of current pest management. The study emphasizes the need of locally informed management strategies for optimal control and prevention in rapidly urbanizing landscapes like Central Punjab.